Composite current collector with high tensile property and preparation method thereof
By designing a gradient cyclic structure in the composite fluid and forming copper layers of different grain sizes, the problem of insufficient tensile performance of the composite fluid is solved, significantly improving its tensile performance and surface fine structure, and extending the service life of lithium-ion batteries.
Patent Information
- Application Number
- CN202411724706.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
AI Technical Summary
The tensile performance of the composite fluid collector is insufficient, resulting in easy belt breakage in the high-speed lamination production process, affecting production efficiency and may cause safety problems.
By designing a gradient cyclic structure, a copper layer with different grain sizes is formed, and a composite fluid with high tensile performance is prepared. The method includes pretreating the flexible substrate, and dynamically adjusting the additive content by adjusting the electrolyte temperature and current density to form a copper layer in turn.
It significantly improves the tensile performance of the composite fluid collection, reduces the surface roughness, inhibits the formation of surface cracks, and extends the service life of lithium-ion batteries.
Smart Images

Figure CN119517996A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of current collectors, and in particular relates to a composite current collector with high tensile properties and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are the core of modern electronic devices, and current collectors play a vital role in them. The main function of current collectors is to carry positive and negative electrode materials and effectively collect and transfer electrons to ensure efficient operation of the battery. However, traditional current collectors have many defects, which not only affect the performance of the battery, but also pose a threat to safety.
[0003] Traditional current collectors are mostly made of metal foil materials, such as copper foil and aluminum foil. Although they have good conductivity, they are expensive to manufacture. In addition, these materials have poor tensile strength and are prone to large burrs. The burrs may puncture the battery separator, causing the positive and negative electrode solutions to mix, thus causing safety accidents. These defects make it difficult for traditional current collectors to meet the modern market's demand for high-performance batteries.
[0004] In order to solve these problems, composite current collectors have become a research direction that has attracted much attention. Composite current collectors adopt a multilayer structure design, combining the advantages of different materials, maintaining good conductivity while reducing preparation costs. This makes it a new material with great potential in lithium-ion batteries. However, despite the many advantages of composite current collectors, their development is still limited by some key factors.
[0005] One of the main limitations is the insufficient tensile properties of the composite current collector. This defect makes it difficult to adapt to the high-speed lamination production process during production and use. High-speed lamination is an important technology to improve production efficiency, but the composite current collector is prone to band breakage during this process, which seriously affects production efficiency. In addition, poor tensile properties may inhibit the full performance of product functions and even cause functional failure, which in turn causes safety issues.
[0006] Therefore, overcoming the defect that the tensile performance of the composite current collector is not as good as that of the composite current collector is a technical problem that needs to be solved urgently in this field.
[0007] It should be noted that the above information disclosed in this background technology section is only used to understand the background technology of the present application concept, and therefore, the above description is not considered to constitute information of the prior art. Summary of the invention
[0008] The embodiments of the present disclosure at least provide a composite current collector with high tensile properties and a method for preparing the same.
[0009] In a first aspect, the present disclosure provides a composite current collector with high tensile properties, comprising: a flexible substrate, and copper layers with at least three grain sizes on both sides of the flexible substrate; the copper layers include an A layer, a B layer, and a C layer, and the grain sizes are related by d A <d B <d C ; The copper layers are arranged in a cyclic order from the upper and lower substrate surfaces of the flexible substrate as layer A, layer B, layer C, layer C, layer B, layer A, and at least twice; or, the copper layers are arranged in a cyclic order from the upper and lower substrate surfaces of the flexible substrate as layer C, layer B, layer A, layer A, layer B, layer C, and at least twice.
[0010] In an optional embodiment, the size d of the grains is in the range of 20-500 nm.
[0011] In an optional embodiment, the grain size relationship satisfies the following relationship: d B / d A =1.5-3;d C / d B =1.5-3.
[0012] In an optional embodiment, the total thickness L of the single-layer film of the copper layer is in the range of 500-5000 nm.
[0013] In an optional embodiment, the thickness L of the A layer, the B layer and the C layer is A , L B , L C The following relationship is satisfied: A / L B =0.5-1.5; L B / L C =0.5-1.5.
[0014] In an optional embodiment, the copper layer is any one of copper and a copper alloy.
[0015] In an optional embodiment, the flexible substrate is any one of a biaxially oriented polypropylene film, a cast polypropylene film, a polyethylene terephthalate film, a polyimide film and a polyethylene naphthalate film; and the thickness of the flexible substrate is in the range of 3-20 μm.
[0016] In an optional embodiment, the copper layer further includes a D layer, and the grain size relationship is d D / d C =1.5-3, the thickness of the D layer satisfies L C / L D =0.5-1.5.
[0017] In an optional embodiment, the copper layer is arranged in a cyclic order from the upper and lower substrate surfaces of the flexible substrate: A layer, B layer, C layer, D layer, D layer, C layer, B layer, A layer, and at least twice; or, the copper layer is arranged in a cyclic order from the upper and lower substrate surfaces of the flexible substrate: D layer, C layer, B layer, A layer, A layer, B layer, C layer, D layer, and at least twice.
[0018] In the second aspect, the embodiments of the present disclosure also provide a method for preparing a composite current collector with high tensile properties as described above, comprising the following steps: step S1, pretreating a flexible substrate; step S2, adjusting the electrolyte temperature and current density corresponding to the grain size, and dynamically adjusting the additive content, forming copper layers in sequence according to an arrangement cycle order, and obtaining a composite current collector with high tensile properties.
[0019] The beneficial effect of the present invention is that the composite current collector with high tensile performance and the preparation method thereof realize the cyclic growth of the copper layer in grain size and twin thickness at the microscopic level by designing a gradient cycle structure, so that the film layer undergoes additional progressive deformation during the stretching process, expanding from the center to the surface in the positive gradient interval and from the surface to the center in the reverse gradient interval. In the cycle of positive gradient CBA and reverse gradient ABC, the tensile performance of the composite current collector is significantly improved. At the same time, the fine microstructure of the surface can also effectively reduce the surface roughness, inhibit the formation of surface cracks, and extend the service life of the lithium-ion battery.
[0020] Gradient stress and gradient strain are generated due to the gradual yielding of grains with gradient sizes. These gradient stress and strain are formed under uniform deformation, which is different from the strain gradient plasticity usually caused by non-uniform deformation.
[0021] This new material strengthening mechanism provides a new idea for material strengthening by introducing strain gradient in gradient microstructure.
[0022] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description, claims and drawings.
[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 A structural diagram of a composite current collector with high tensile properties according to embodiments 1 to 4 provided in the embodiments of the present disclosure;
[0026] Figure 2 Structural diagram of the high tensile performance composite current collector of Examples 5-8 provided in the embodiments of the present disclosure.
[0027] In the figure:
[0028] 1. Flexible substrate; 2. Layer A; 3. Layer B; 4. Layer C. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.
[0031] Herein, example embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. As used herein, expressions such as "at least one of..." modify the entire list of elements when following a list of elements, rather than modifying individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.
[0032] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.
[0033] In a uniform microstructure, deformation usually starts from the surface and gradually extends to the inside, which manifests itself in the composite current collector as a defect of insufficient strength during tension.
[0034] In addition to tensile properties, surface roughness is also an important factor affecting battery performance. Copper foil with lower surface roughness usually has better conductivity and lower resistance, which helps to reduce the internal resistance of the battery and improve the charging and discharging efficiency and capacity. In addition, copper foil with low roughness can also improve the cycle stability of the battery and extend its service life.
[0035] The defects existing in the above solutions are the results obtained by the inventor after practice and careful research. Therefore, the discovery process of the above problems and the solutions proposed by the present disclosure for the above problems below should be the contributions made by the inventor to the present disclosure during the disclosure process.
[0036] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0037] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0038] The present disclosure provides a composite current collector with high tensile properties, comprising: a flexible substrate, and copper layers with at least three grain sizes on both sides of the flexible substrate; the copper layers include an A layer, a B layer, and a C layer, and the grain sizes are related by d A <d B <d C; The copper layers are arranged in a cyclic order from the upper and lower substrate surfaces of the flexible substrate as layer A, layer B, layer C, layer C, layer B, layer A, and at least twice; or, the copper layers are arranged in a cyclic order from the upper and lower substrate surfaces of the flexible substrate as layer C, layer B, layer A, layer A, layer B, layer C, and at least twice.
[0039] In an optional embodiment, the size d of the grains is in the range of 20-500 nm.
[0040] In an optional embodiment, the grain size relationship satisfies the following relationship: d B / d A =1.5-3;d C / d B =1.5-3.
[0041] In an optional embodiment, the total thickness L of the single-layer film of the copper layer is in the range of 500-5000 nm.
[0042] In an optional embodiment, the thickness L of the A layer, the B layer and the C layer is A , L B , L C The following relationship is satisfied: A / L B =0.5-1.5; L B / L C =0.5-1.5.
[0043] In an optional embodiment, the copper layer is any one of copper and copper alloy, and the copper sample has a nano twin structure that gradually changes from the surface to the inside, which can effectively improve the strength and work hardening ability of the material, and the purity of the copper is not less than 99.99%.
[0044] In an optional embodiment, the flexible substrate is any one of a biaxially oriented polypropylene film (OPP), a cast polypropylene film (CPP), a polyethylene terephthalate film (PET), a polyimide film (PI) and a polyethylene naphthalate film (PEN); and the thickness of the flexible substrate ranges from 3 to 20 μm.
[0045] In an optional embodiment, the copper layer further includes a D layer, and the grain size relationship is d D / d C =1.5-3, the thickness of the D layer satisfies L C / L D =0.5-1.5.
[0046] In an optional embodiment, the copper layer is arranged in a cyclic order from the upper and lower substrate surfaces of the flexible substrate: A layer, B layer, C layer, D layer, D layer, C layer, B layer, A layer, and at least twice; or, the copper layer is arranged in a cyclic order from the upper and lower substrate surfaces of the flexible substrate: D layer, C layer, B layer, A layer, A layer, B layer, C layer, D layer, and at least twice.
[0047] The disclosed embodiment also provides a method for preparing a composite current collector with high tensile properties as described above, comprising the following steps: step S1, pretreating a flexible substrate; step S2, adjusting the electrolyte temperature and current density corresponding to the grain size, and dynamically adjusting the additive content, forming copper layers in sequence according to an arrangement cycle order, and obtaining a composite current collector with high tensile properties.
[0048] Three homogeneous nano-copper layers (A, B, C) with different (grain sizes) were prepared by direct current electrodeposition technology. The electrolyte temperatures were 25℃, 30℃ and 35℃, respectively, and the current densities of the corresponding films were 3A / dm 2 , 4A / dm 2 , 5A / dm 2 , and dynamically adjust the content of additives in the corresponding film layer.
[0049] Samples I and II with spatial gradient order were synthesized at different temperatures according to a specific gradient order (A→B→C→C→B→A and C→B→A→A→B→C). The temperature change process of I was gradually increased from 25°C to 35°C, and then decreased from 35°C to 25°C, and the corresponding current density was used at the corresponding temperature; while the temperature change process of II was first decreased from 35°C to 25°C, and then increased from 25°C to 35°C, and the corresponding current density was used at the corresponding temperature.
[0050] Specifically, the influence of temperature on the preparation process is mainly reflected in the following aspects:
[0051] (1) Changes in temperature affect the thickness and grain size of the sample. Specifically, as the temperature increases, the twin thickness and grain size increase. During the preparation process, the temperature was gradually increased from 25°C to 35°C and then gradually decreased to 25°C, and a sample with a specific gradient order could be synthesized.
[0052] (2) The structural gradient caused by temperature changes will affect the mechanical properties of the material. For example, an increase in temperature will cause the grain size to increase, thereby affecting the yield strength and work hardening behavior of the material. Different temperature gradient sequences (such as from low temperature to high temperature or from high temperature to low temperature) will result in different mechanical properties.
[0053] (3) Temperature changes can affect the surface roughness of materials. Higher temperatures may lead to larger grain sizes, which in turn increase surface roughness. During the stretching process, a surface structure with finer grains can effectively reduce the surface roughening phenomenon.
[0054] Specifically, temperature plays a key role in the sample preparation process, affecting the material's microstructure and mechanical properties. By controlling the temperature gradient, the material's properties can be adjusted to meet specific application requirements.
[0055] Physical performance test:
[0056] 1. Tensile strength: Test according to Appendix D of GB / T5230-1995.
[0057] 2. Surface roughness: inspect according to Appendix A of SJT11483-2014.
[0058]
[0059]
[0060] Specifically, it can be seen from Comparative Examples 1 and 2 and Examples 1-8 that the gradient cycle preparation process can significantly improve the tensile strength of the film layer and reduce the surface roughness of the film layer.
[0061] Specifically, from the comparison between Examples 1-4 and Examples 5-8, it can be seen that under the same preparation process, the samples prepared by the C→B→A→A→B→C cycle have higher tensile strength and lower surface roughness than those prepared by the A→B→C→C→B→A cycle. This is because during the deformation process, the copper samples in the positive gradient order exhibit a larger strain gradient, which leads to stronger constraints and helps to inhibit surface roughening and crack formation.
[0062] Specifically, when the copper layer undergoes plastic deformation, the deformation starts from the center of the sample and then gradually expands to the surface. This gradual deformation mechanism helps to evenly distribute stress and avoid local stress concentration.
[0063] In summary, the composite current collector with high tensile performance and its preparation method realize the cyclic growth of the copper layer in grain size and twin thickness at the microscopic level by designing a gradient cycle structure, so that the film layer undergoes additional progressive deformation during the stretching process, expanding from the center to the surface in the positive gradient range and from the surface to the center in the reverse gradient range. The tensile performance of the composite current collector is significantly improved in the cycle of positive gradient and reverse gradient. At the same time, the fine microstructure on the surface can effectively reduce the surface roughness, inhibit the formation of surface cracks, and extend the service life of the lithium-ion battery.
[0064] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A composite current collector with high tensile properties, characterized in that: include: A flexible substrate, copper layers of at least three grain sizes on both sides of the flexible substrate; The copper layer includes layer A, layer B and layer C, and the grain size relationship is d A <d B <d C ;as well as The copper layer is arranged from the upper and lower substrate surfaces of the flexible substrate in a cyclic order of layer A, layer B, layer C, layer C, layer B, layer A, and the cycle is at least two times; Alternatively, the copper layers are arranged in a cyclic order of C layer, B layer, A layer, A layer, B layer, and C layer from the upper and lower substrate surfaces of the flexible substrate, and the cycle is repeated at least twice.
2. The composite current collector with high tensile properties according to claim 1, characterized in that: The size d of the grains is in the range of 20-500 nm.
3. The composite current collector with high tensile properties according to claim 1, characterized in that: The grain size relationship satisfies the following relationship: d B / d A =1.5-3; d C / d B =1.5-3。 4. The composite current collector with high tensile properties according to claim 1, characterized in that: The total thickness L of the single-layer film of the copper layer is in the range of 500-5000 nm.
5. The composite current collector with high tensile properties according to claim 1, characterized in that: The thickness L of the A layer, the B layer and the C layer A , L B , L C The following relationship is satisfied: L A / L B 0.5-1.5; L B / L C 0.5-1.
5.
6. The composite current collector with high tensile properties according to claim 1, characterized in that: The copper layer is any one of copper and copper alloy.
7. The composite current collector with high tensile properties according to claim 1, characterized in that: The flexible substrate is any one of a biaxially oriented polypropylene film, a cast polypropylene film, a polyethylene terephthalate film, a polyimide film and a polyethylene naphthalate film; The thickness of the flexible substrate is in the range of 3-20 μm.
8. The composite current collector with high tensile properties according to claim 1, characterized in that: The copper layer also includes a D layer, and the grain size relationship is d D / d C =1.5-3, the thickness of the D layer satisfies L C / L D =0.5-1.
5.
9. The composite current collector with high tensile properties according to claim 8, characterized in that: The copper layer is arranged from the upper and lower substrate surfaces of the flexible substrate in a cyclic order of A layer, B layer, C layer, D layer, D layer, C layer, B layer, A layer, and the cycle is at least two times; Alternatively, the copper layers are arranged in a cyclic order from the upper and lower substrate surfaces of the flexible substrate: D layer, C layer, B layer, A layer, A layer, B layer, C layer, D layer, and the cycle is repeated at least twice.
10. A method for preparing a composite current collector with high tensile properties as claimed in any one of claims 1 to 9, characterized in that: The steps include: Step S1, pre-treating the flexible substrate; Step S2, adjusting the electrolyte temperature and current density corresponding to the grain size, and dynamically adjusting the additive content, forming copper layers in sequence according to the arrangement cycle order, and obtaining a composite current collector with high tensile properties.